A reconfigurable and automatic platform for the on-demand production of stretchable conductive composites. (1st April 2023) - Lu, Hongda; Zhang, Qingtian; Huang, Xumin; Cole, Tim; Yun, Guolin; Zhang, Yuxin; Qiao, Ruirui; Li, Weihua; Tang, Shi-Yang
Abstract: Stretchable conductive composites (SCCs) have been widely used as interconnects and sensors in stretchable electronic devices due to their tunable electromechanical properties and intrinsically high stretchability compared to solid metals. SCCs can be readily made by mixing (or breaking bulk) conductive fillers within an elastomeric polymer, which are subsequently cured. Despite the simplicity of this, most fabrication methods follow customized protocols and lack precise automatic control. These methods also require bulky and costly equipment (e.g. stirrers, mixers, ovens, and vacuuming machines). Also, variations in the production process make it challenging to maintain the consistency of SCC's electrical and mechanical properties produced in different batches. To solve this problem, this work develops an automatic SCC production platform (ASPP) that can be programmed to produce SCCs with high consistency in properties. The versatility of ASPP is demonstrated by fabricating SCCs with single and hybrid fillers, and porous structures. The consistency of SCCs' electromechanical properties is examined using samples fabricated in different batches following the same protocol. We further utilize the fabricated SCCs to realize various intelligent tactile sensing and heating platforms. The capability demonstrated for the ASPP shows its potential in fabricating SCCs for applications in soft robotics and wearable devices.